Continuous pre- and post-transplant exposure to a disease-associated gut microbiome promotes hyper-acute graft-versus-host disease in wild-type mice. (3rd July 2020) - Bowerman, Kate L; Varelias, Antiopi; Lachner, Nancy; Kuns, Rachel D; Hill, Geoffrey R; Hugenholtz, Philip
ABSTRACT: Objective: The gut microbiome plays a key role in the development of acute graft-versus-host disease (GVHD) following allogeneic hematopoietic stem cell transplantation. Here we investigate the individual contribution of the pre- and post-transplant gut microbiome to acute GVHD using a well-studied mouse model. Design: Wild-type mice were cohoused with IL-17RA –/ – mice, susceptible to hyperacute GVHD, either pre- or post-transplant alone or continuously (i.e., pre- and post-transplant). Fecal samples were collected from both WT and IL-17RA –/ – mice pre- and post-cohousing and post-transplant and the microbiome analyzed using metagenomic sequencing. Results: Priming wild-type mice via cohousing pre-transplant only is insufficient to accelerate GVHD, however, accelerated disease is observed in WT mice cohoused post-transplant only. When mice are cohoused continuously, the effect of priming and exacerbation is additive, resulting in a greater acceleration of disease in WT mice beyond that seen with cohousing post-transplant only. Metagenomic analysis of the microbiome revealed pre-transplant cohousing is associated with the transfer of specific species within two as-yet-uncultured genera of the bacterial family Muribaculaceae; CAG-485 and CAG-873 . Post-transplant, we observed GVHD-associated blooms of Enterobacteriaceae members Escherichia coli and Enterobacter hormaechei subsp. steigerwaltii, and hyperacute GVHD gut microbiome distinct from that associated with delayed-onset disease (>10 days post-transplant). Conclusion: These results clarify the importance of the peri-transplant microbiome in the susceptibility to acute GVHD post-transplant and demonstrate the species-specific nature of this association.